Manajemen Proyek Dalam Pengembangan Dan Kemajuan Wisata Prapat (Danau Toba) 2021 - Diana Suita; Haida Dafitri; Marina Elsera; Liza Fitriana (LPPM STIKOM Tunas Bangsa, 2021)
Lake Toba is the location of a visited tourist area and one of the interesting places for both domestic and foreign tourists to visit. For this reason, the Ministry of Public Works and Public Housing (PUPR) continues to organize 5 Priority National Tourism Strategic Areas (KSPN), namely Lake Toba, Borobudur, Mandalika, Labuan Bajo and Manado - Likupang. It aims to support economic recovery, particularly the tourism sector in a new era of normality. The progress of the Government to immediately renovate and develop tourist areas, renovate and carry out the construction of traditional houses, amphitheater, sopo bolon houses, Anting Anting houses, coffee shops, information centers and so on for the progress of Prapat (Lake Toba). different from what is originally planned. Such as the renovation of the Sopo Bolon House and the Anting Anting House. Traditional houses consist of wood. However, nowadays it is very difficult to get wood like in the previous traditional houses. Several other things hamper progress on site. For that we need proper management in a project work The Community Service Team of Universitas Harapan Medan carried out socialization activities for the Management of Tourism Area Development in terms of renovation progress and project implementation with residents around the Sialagan (Batu Kursi) and Hutaraja areas.